Heavy metals content in sweet potato (Ipomoea batatas L.) grown on soil contaminated by gold mine tailings with composted cow manure amendment - Rhazista Noviardi; Agung Karuniawan; Emma Trinurani Sofyan; Pujawati Suryatmana (Brawijaya University, 2023)
Artisanal gold miners usually dispose of gold mine tailings in storage ponds or agricultural land used for farming. However, the gold mine tailings still contain heavy metals such as cadmium, copper, lead, and zinc and can lead to bioaccumulation in food chains. This study investigated the influence of composted cow manure as organic fertilizer on heavy metals (Cd, Cu, Pb and Zn) content in sweet potatoes grown on soil contaminated by gold mine tailing. The MZ119 clone sweet potato plants were grown on soils added with mixtures of gold mine tailings at ratios of 0% (control), 30%, 50%, 70%, and 100% (w/w), and composted cow manure (0, 250, 500, and 750 g/10 kg of soil). The results showed that the higher the ratio of gold mine tailings to the soil, the higher the accumulation of metals in sweet potatoes. According to the translocation factor (TF) value, heavy metals (Cd, Cu, Pb and Zn) accumulated higher in the shoots than in the roots of sweet potatoes. Accumulation of heavy metals in sweet potato occurred in the following order: Zn>Cu>Pb>Cd. This study recommends that sweet potatoes could be used for the phytoremediation of heavy metals (Cd, Cu, Pb and Zn) in polluted soils, but the plants may not be used for consumption.